Introduction : À quoi (et à qui) servent les traîtres ? - Rachel Renault; Sébastien Schick (L'Atelier du CRH)
The aim of this dossier is to examine how the charge of treason is made. Why label an individual a traitor, or describe an act as treason? What are the benefits? And under what conditions can the operation of disqualification succeed? Treason can take place on an interpersonal level, in the form of a breach of informal norms, or as a judicial qualification. Each time, it fulfils a function: it reconfigures the contours of a group or the modalities of a social relationship by sanctioning a defection, reclassified as a sin, crime or fault. Certain agents profit from this reclassification. From the betrayed word to the breach of state security, and from the sixteenth to the twentieth century, this dossier endeavours to offer a common reading of treason as an observatory of social configurations and normative regimes over time